Profil Cabang Olahraga Unggulan Papua (Studi Deskriptif Berdasarkan Perolehan Medali) - Ita, saharuddin (Journal of Sport Science and Education, 2017)
Â Abstraks: The purpose of this study was to see the profile of the sport featured on the side of the medals Papua fifth consecutive PON. The method used is descriptive method to verify the data sport that gained the gold medal in the last 5 PON. Pupolasi in this study were all built Koni sport Papua province where 42 sports. While the sample is a sport that gained medals in the last 5 PON. Result. Sports that consistently win gold medals in bertut 5 Last PON respectively were athletics, PODSI (Canoes, kayaks, dragon boats) Â and PABBSI (weightlifting, weight lifting and body building) as the flagship sport of Papua.Â